KAJIAN YURIDIS TENTANG TANGGUNG JAWAB PEMERINTAH DAERAH TERHADAP PENGELOLAAN PENDIDIKAN DASAR DAN MENENGAH (SUATU PENELITIAN DI KABUPATEN PIDIE) - Sayed Muhajjir; Husni Jalil; Mahdi Syahbandir (Jurnal Ilmu Hukum, 2016)
Abstract: Law Number 20/ Year 2003 regarding the National Education System confidently states the rights and responsibilities of both - the central and local government by the management of education. Article 13 letter b and c of the local regulation or known as Aceh Qanun No. 11/ Year 2014 also confirmed that the Government of Aceh and district/ municipal governments in accordance to their authorities are obliged to ensure the implementation of highly qualified, equitable, fair and islamic-based education and to provide teaching- and educational-staffs as required by the educational unit. The objectives of this research were to: i) explain the responsibilities of local government by the management of primary and secondary education in Pidie district regency, ii) observe the effectiveness of legislation regarding the responsibility of local government, iii) explain the supporting and inhibiting factors by the implementation of primary- and secondary-education management. Results showed that still, there have been some obstacles and empirical barriers that have to be tackled by the implementation of primary- and secondary-education management in the Pidie district regency, especially in terms of inadequate educational facilities and supporting agents similar to those commonly experienced by the schools located in remote and rural areas, uneven distribution in terms of quantity and highly qualified teachers among schools located in remote areas, number of broke-up school children at all three levels; the elementary, junior and senior high schools. These three things are actually the responsibilities and authorities of local government, which have been constituted in the legislation norms and to be implemented maximally and effectively.Keywords: local government, primary and secondary education, responsibility. Abstrak: Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional secara tegas mengatur mengenai hak dan kewajiban keduanya – pemerintah pusat dan daerah terhadap pengelolaan pendidikan. Pasal 13 huruf b dan c peraturan daerah atau dikenal sebagai Qanun Aceh No.11/ Tahun 2014 juga menegaskan bahwa Pemerintah Aceh dan pemerintah kabupaten/kota sesuai dengan kewenangannya berkewajiban untuk menjamin penyelenggaraan pendidikan yang bermutu, merata, adil dan berdasarkan azas islam dan menyediakan tenaga pendidik dan tenaga kependidikan sesuai kebutuhan satuan pendidikan. Tujuan yang hendak dicapai dalam penelitian ini adalah untuk: i) menjelaskan mengenai tanggung jawab pemerintah daerah terhadap pengelolaan pendidikan dasar dan menengah di kabupaten Pidie, ii) melihat sejauh mana efektivitas peraturan perundang-undangan menyangkut tanggung jawab pemerintah daerah, iii) menjelaskan faktor pendukung dan penghambat dalam pelaksanaan pengelolaan pendidikan dasar dan menengah. Hasil penelitian menunjukkan bahwa masih adanya masalah dan kendala empiris yang perlu diatasi dalam pelaksanaan pengelolaan pendidikan dasar dan menengah di kabupaten Pidie, terutama belum memadainya sarana dan prasarana pendidikan seperti yang dialami oleh sekolah-sekolah daerah terpencil maupun pedesaan pada umumnya, penyebaran yang tidak merata dalam hal jumlah guru dan guru yang berkwalitas diantara sekolah-sekolah terletak di daerah terpencil, jumlah anak-anak putus sekolah di tiga level; pendidikan SD, SMP dan SMA. Ketiga hal tersebut sebenarnya merupakan tanggung jawab dan kewenangan pemerintah daerah, yang telah diatur berdasarkan norma peraturan perundang-undangan dan harus diimplementasikan secara maksimal dan efektif.Kata kunci: pemerintah daerah, pendidikan dasar dan menengah, tanggung jawab.